INTEGRITAS DAN KERETAKAN PRIBADI - Askolan Lubis (Universitas Islam Negeri Sumatera Utara Medan, 2017)
Every human being has diverse needs, both physical and psychological needs. If someone fails to meet their needs, it is likely to cause frustration, and frustration itself always contains tension. If tension continues to be experienced, then of course the emergence of inner conflict in a person that results in disruption of the person's personal integrity. In order for the elements in a person's personality to work harmoniously and there is no personal rift, a strong religious soul is needed so that it is expected that a human being who is istiqomah, resigns to God, will be grateful if he is successful and be patient when he fails.Keywords: integrity, rift, personal